Cultural Values and Behavior: Chineseness within Geographic Boundaries - Ellis, Seth (Institutional Knowledge at Singapore Management University, 1985)
This exploratory study suggests that traits associated with the ethnic identity of one culture may be exhibited by a substantial portion of the population of another culture. The trait of Chineseness was measured in an American sample and it is demonstrated that this trait and certain associated behaviors were exhibited by a significant portion of the sample.